40Ar/39Ar age of the onset of high-Ti phase of the Emeishan volcanism strengthens the link with the end-Guadalupian mass extinction. Issue 15 (18th November 2018) - Li, Youjuan; He, Huaiyu; Ivanov, Alexei V.; Demonterova, Elena I.; Pan, Yongxin; Deng, Chenglong; Zheng, Dewen; Zhu, Rixiang
ABSTRACT: Precise time constraints of the main extrusive phase of the Emeishan large igneous province (ELIP) remain unresolved because basalts commonly do not contain suitable minerals for U–Pb dating, whereas previous 40 Ar/ 39 Ar studies on basalts yielded tectonothermal overprint ages. The timing for the ELIP was deduced from indirect dating of minor intrusions of ultramafic/mafic and felsic compositions by geochronological methods and geological correlations. The extrusive part of the ELIP consists of an older low-Ti and younger high-Ti basalt phases. We have found fresh samples of plagioclase-phyric rocks at the lower Qiaojia extrusive section (the Yunnan province of China), which belong to the ELIP unit of the high-Ti basalt series. 40 Ar/ 39 Ar dating on plagioclase from two samples conducted at two different laboratories using different age standards yielded statistically indistinguishable results with the weighted mean age of 260.1 ± 1.2 Ma for five individual measurements. This provides the direct constraints on the onset of the ELIP high-Ti basalt extrusive phase. The obtained age is within the error or slightly older than the age of the Guadalupian–Lopingian boundary and felsic ignimbrite capping the ELIP lava succession (both dated at 259.1 ± 0.5 Ma). Our new data are strengthening the short duration of the, at least, high-Ti phase of the ELIP volcanism and its temporal link with the end-Guadalupian mass extinction. Estimation of the total duration of the ELIP volcanism awaits finding of suitable for dating low-Ti basalts.